Assessing the Role of Community Participation in Mediating the Impact of Social Financial Practices on Business Performance in Indonesia’s Palm Oil Industry - Nugroho, Budi Sulistiyo; Judijanto, Loso; Sudarmanto, Eko (Eastasouth Institute, 2024)
The Indonesian palm oil industry is critical in the national economy, yet it faces significant social and environmental challenges. This study investigates the mediating role of community participation in the relationship between social financial practices and business performance in this sector. Using a quantitative approach, data were collected from 180 respondents through a structured survey and analyzed using Structural Equation Modeling-Partial Least Squares (SEM-PLS 3). The findings indicate that community participation positively impacts business performance and strengthens the effectiveness of social financial practices. Social financial practices, which integrate social and environmental considerations into financial decision-making, were shown to significantly enhance business performance, especially when supported by active community engagement. These results underscore the importance of community involvement in implementing socially responsible finance and highlight its role in promoting sustainable business practices. The study contributes to the literature on sustainable finance and stakeholder engagement by providing empirical evidence on the interdependent roles of community participation and social finance in achieving business success in the palm oil industry.